2020
DOI: 10.5194/essd-12-2811-2020
|View full text |Cite
|
Sign up to set email alerts
|

Greenland liquid water discharge from 1958 through 2019

Abstract: Abstract. Greenland runoff, from ice mass loss and increasing rainfall, is increasing. That runoff, as discharge, impacts the physical, chemical, and biological properties of the adjacent fjords. However, where and when the discharge occurs is not readily available in an open database. Here we provide data sets of high-resolution Greenland hydrologic outlets, basins, and streams, as well as a daily 1958 through 2019 time series of Greenland liquid water discharge for each outlet. The data include 24 507 ice ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(130 citation statements)
references
References 89 publications
3
127
0
Order By: Relevance
“…However, exactly where, when, and how that mass has been lost is not precisely known. There are three common methods for estimating mass balance -changes in gravity (Barletta et al, 2013;Groh et al, 2019;The IMBIE Team, 2019;Velicogna et al, 2020), changes in volume (Simonsen et al, 2021a;Sørensen et al, 2011;Zwally and Giovinetto, 2011;Sasgen et al, 2012;Smith et al, 2020), or the input/output (IO) method (Colgan et al, 2019;Rignot et al, 2019). Each provides some estimate of where, when, and how the mass is lost or gained, and each method has some limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exactly where, when, and how that mass has been lost is not precisely known. There are three common methods for estimating mass balance -changes in gravity (Barletta et al, 2013;Groh et al, 2019;The IMBIE Team, 2019;Velicogna et al, 2020), changes in volume (Simonsen et al, 2021a;Sørensen et al, 2011;Zwally and Giovinetto, 2011;Sasgen et al, 2012;Smith et al, 2020), or the input/output (IO) method (Colgan et al, 2019;Rignot et al, 2019). Each provides some estimate of where, when, and how the mass is lost or gained, and each method has some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we introduce the new PROMICE Greenland ice sheet mass balance dataset based on the IO method, updating the previous product from Colgan et al (2019). IO inputs are the positive SMB fields from one RCM (1840RCM ( through 1985 to three RCMs (1986 onward), IO outputs are the negative SMB fields from the same RCM(s), the basal mass balance, and an estimate of dynamic ice discharge.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that our measurements were utilized for validation of daily discharge from all Greenlandic drainage basins estimated from output of two regional climate models (Mankoff and others, 2020). The comparison of the data from 2017 to 2019 indicated that one of the models (MAR) (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A recent synthesis showed that SMB models vary considerably given the same forcing, and readers are referred to this and other literature for further information on why these models might disagree. Smith et al (2017) and Mankoff et al (2020) have both explored what these differences mean for water exiting the GrIS, but our purpose is to demonstrate the importance of coupling SMB model output with a surface flow routing model to understand runoff transport before it enters the englacial system. This enables rigorous estimation of supraglacial flow accumulation and Figure 7.…”
Section: Discussionmentioning
confidence: 99%